2015
DOI: 10.1590/0100-2945-208/14
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY AND STRUCTURE OF Oenocarpus mapora GERMPLASM CONSERVED AT EASTERN AMAZON

Abstract: -The aim of this study was to evaluate the genetic diversity and structure in the germoplasm of Oenocarpus mapora conserved at Eastern Amazon. Thus, 88 individuals were genotyped with five microsatellite loci. These individuals belong to 24 accessions that were sampled in eight sample places of three Brazilian Amazon states conserved at the Active Germplasm Bank (AGB) of Embrapa Eastern Amazon. All loci were polymorphic and they generated 85 alleles with an average of 17 alleles per loci. Total genetic diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other population genetic structure parameters, such as Wright's inbreeding coefficient and gene flow, have shown that, in general, genetic differentiation (F ST ) is low, indicating genetic variation higher within -rather than among -populations and a high gene flow among populations (Elshibli and Korpelainen, 2008;Martins-Corder et al, 2009;Shapcott et al, 2009;Namoff et al, 2011;Silva et al, 2011;Giovino et al, 2014;Nazareno and dos Reis, 2014;Oliveira et al, 2014;Moura et al, 2015). Recently, Ramos et al (2016) found a high level of genetic diversity, mostly within populations, for adults and seedlings in populations of A. aculeatum, and along with results for spatial genetic structure indicated short-distance seed dispersal and modest levels of pollen flow.…”
Section: Introductionmentioning
confidence: 99%
“…Other population genetic structure parameters, such as Wright's inbreeding coefficient and gene flow, have shown that, in general, genetic differentiation (F ST ) is low, indicating genetic variation higher within -rather than among -populations and a high gene flow among populations (Elshibli and Korpelainen, 2008;Martins-Corder et al, 2009;Shapcott et al, 2009;Namoff et al, 2011;Silva et al, 2011;Giovino et al, 2014;Nazareno and dos Reis, 2014;Oliveira et al, 2014;Moura et al, 2015). Recently, Ramos et al (2016) found a high level of genetic diversity, mostly within populations, for adults and seedlings in populations of A. aculeatum, and along with results for spatial genetic structure indicated short-distance seed dispersal and modest levels of pollen flow.…”
Section: Introductionmentioning
confidence: 99%
“…pataua Mart. 4 . Oenocarpus distichus (also known as bacaba-de-leque) has high potential in the palm and processed pulp markets, including its use in the production of “bacaba wine”, a nutritious energy drink with commercial potential similar to that of Euterpe oleracea Mart.…”
Section: Introductionmentioning
confidence: 99%
“…This is necessary for breeding programs to conserve native populations in extractive areas. Oenocarpus distichus genetic improvement and conservation programs depend on fruits biometric characterization and genetic parameter studies of genotypes showing promise for germplasm banks and conservation programs of this plant 4,10 .…”
Section: Introductionmentioning
confidence: 99%